2019
DOI: 10.32872/spb.v14i3.37393
|View full text |Cite
|
Sign up to set email alerts
|

Situational Factors Influencing Receptivity to Bullshit

Abstract: Individuals are motivated to maintain a sense of meaning, and enact cognitive processes to do so (e.g., perceiving structure in the environment). This motivation to find meaning may ultimately impact humans’ interpretation of "bullshit", statements intended to convey profundity without any meaning. Conversely, subtle cues threatening the meaningfulness of bullshit may elicit greater skepticism. Three studies tested situational factors predicted to heighten or diminish susceptibility to bullshit by changing mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…A pattern of suggestions can be seen in various empirical studies that have been carried out on susceptibility to bullshit (Bolton, 2015; Pennycook et al, 2015), sensitivity to bullshit (Erlandsson et al, 2018), receptivity of bullshit (Brown, Keefer and McGrew, 2019), and the correlation between pseudo‐profound and scientific bullshit (Evans et al, 2020). The studies suggest that vulnerability to bullshit increases with low levels of intelligence.…”
Section: The Unity and The Separation Viewsmentioning
confidence: 98%
See 1 more Smart Citation
“…A pattern of suggestions can be seen in various empirical studies that have been carried out on susceptibility to bullshit (Bolton, 2015; Pennycook et al, 2015), sensitivity to bullshit (Erlandsson et al, 2018), receptivity of bullshit (Brown, Keefer and McGrew, 2019), and the correlation between pseudo‐profound and scientific bullshit (Evans et al, 2020). The studies suggest that vulnerability to bullshit increases with low levels of intelligence.…”
Section: The Unity and The Separation Viewsmentioning
confidence: 98%
“…Pennycook et al found that people who were more receptive to bullshit were those who were low in the capacity for reflective thinking and cognitive ability, likely to hold religious and paranormal beliefs, and likely to endorse alternative medicine (Pennycook et al, 2015; Čavojová et al, 2020). Other studies also suggest that bullshit predicts diminished prosocial behaviour (Erlandsson et al, 2018), rises with a heightened presumption of meaningfulness (Brown et al, 2019), and serves as a low‐cost strategy for impressing other people (Turpin et al, 2019). Conversely, successful producers of bullshit are rated more intelligent than others (Turpin et al, 2020).…”
Section: Understanding Bullshitmentioning
confidence: 99%